PENGARUH VARIASI FRAKSI VOLUME KOMPOSIT POLYESTER-SERAT KULIT JAGUNG (Zea Mays) TERHADAP KEKUATAN IMPAK, BENDING, DAN TARIK - Akhmad Syarief; Muhammad Amin (Scientific Journal of Mechanical Engineering Kinematika, 2016)
One of the engineering materials is Composite. Composite is a material formed from a combination of two or more matrials that have stronger mechanical properties than the. The composite consists of two parts: a matrix as a binder or a composite protector and a filler as a composite filler. Natural fibers are an alternative filler, and the corn husk fiber (Zea Mays) is one of the many natural fibers grown in the Tanah Laut area of South Kalimantan.From the result of the research, the effect of volume fraction on the composite has the fiber skin fiber which has the highest strength for the impact price that is on the fiber with the volume fraction of 1% 99% fiber polyester corn fiber fiber which has the impact price of 0.0338 joule / mm2. In the highest strength bending test that is on the composite with a fraction of fiber volume of 3% that has a bending power of 3,5775MPa. And in composite tensile test, volume fraction 4% fiber 96% polyester and 5% fiber 95% polyrster have the same value of highest strength that is tensile pull of 1,7991 MPa.